Segun lo que a nuestra celsitud pertenece: Peter the Ceremonious’s appearance (1336-1387) through medieval texts and images (History Journal «Jerónimo Zurita», 2024)
This study offers an analysis of the most relevant aspects concerning the physical presence of Peter the Ceremonious, who, with his complex personality, was very conscious of the pre-eminence of his rank and dignity. To carry out this study, textual sources (mainly his chronicle and the Ordinacions of his house and court) has been resorted. But also, the iconographic representations of his person which, as will be seen, are very eloquent of the kind of political theology the king orchestrated under his reign.
Keywords: Peter the Ceremonious; Crown of Aragon; Iconography; Ceremonial; Ordinacions